HUKUM ISLAM DALAM PEMIKIRAN ULAMA MADURA (Analisis KitabBulghah At-Thullab Karya KH. Thaifur Ali Wafa, Ambunten Timur, Sumenep) - Moh. Afandi (Et-Tijarie, 2018)
AbstractThe treasures of Islamic scholarship have long been known to be very strong with their literary traditions. For this reason, the influence of Imam Madhab is still strong even though it has been adrift hundreds of years from our time. This is because the inheritance of classical Islam in the form of manuscripts by previous ulama is still able to be revived so as to produce new works that are quite coloring for the treasures of Islam in the next era. One of them is the book Bulghath At-Thullab by KH. Thaifur Ali Wafa, a charismatic cleric from Sumenep Madura. This one work experienced a unique phenomenon, because it was born in the modern era, but was able to present the scent of classical fiqh. Keywords: Flexible, Islamic Law, Ulama, Madura, Kitab AbstrakKhazanah keilmuan Islam sejak dahulu dikenal sangat kuat dengan tradisi literasinya. Sebab itulah, pengaruh Imam Madzhab masih kuat meskipun sudah terpaut ratusan tahun dari zaman kita saat ini. Tidak lain hal itu karena warisan Islam klasik yang berupa naskah-naskah karya ulama terdahulu masih mampu dihidupkan kembali sehingga melahirkan karya-karya baru yang cukup mewarnai bagi khazanah Islam di era berikutnya.  Salah satunya adalah kitab Bulghath At-Thullab karya KH. Thaifur Ali Wafa, seorang ulama karismatik asal Sumenep Madura. Karya yang satu ini mengalami fenomena yang unik, karena lahir di era modern, namun mampu menghadirkan aroma fiqh klasik. Kata Kunci: Fleksibel, Hukum Islam, Ulama, Madura, Kitab